Biosynthesis of anti-proliferative gold using endophytic fusarium oxysporum strain isolated from neem (A-indica) leaves - Siddiqui, Ejaz Ahmad; Ahmad, Absar; Julius, Anju; Syed, Asad; Khan, Shadab; Kharat, Mahesh; Pai, Kalpana; Kadoo, Narendra Y.; Gupta, Vidya (Current topics in medicinal chemistry, 2016)
Here we report a simple, rapid, environment friendly approach for the synthesis of gold nanoparticles using neem (Azadirachta indica A. Juss.) fungal endophyte, which based upon morphological and cultural characteristics was eventually identified as Fusarium oxysporum. The aqueous precursor (HAuCl4) solution when reacted with endophytic fungus resulted in the biosynthesis of abundant amounts of well dispersed gold nanoparticles of 10-40 nm with an average size of 22nm. These biosynthesized gold nanoparticles were then characterized by standard analytical techniques such as UV-Visible spectroscopy, X-ray diffraction, Transmission Electron Microscopy and Fourier Transform Infrared Spectroscopy. Cytotoxic activity of these nanoparticles was checked against three different cell types including breast cancer (ZR-75-1), Daudi (Human Burkitt's lymphoma cancer) and normal human peripheral blood mononuclear cells (PBMC), where it was found that our gold nanoparticles are anti-proliferative against cancer cells but completely safe toward normal cells. In addition to this, assessment of toxicity toward human RBC revealed less than 0.1 % hemolysis as compared to Triton X-100 suggesting safe nature of our biosynthesized gold nanoparticles on human cells. Also, our nanoparticles exhibited no anti-fungal (against Aspergillus niger) or anti-bacterial [against Gram positive (Bacillus subtilis & Staphylococcus aureus) and Gram negative (Escherichia coli & Pseudomonas aeruginosa) bacteria] activity thus suggesting their non-toxic, biocompatible nature. The present investigation opens up avenues for eco-friendly, biocompatible nanomaterials to be used in a wide variety of application such as drug delivery, therapeutics, theranostics and so on.

Biological synthesis of alpha-Ag2S composite nanoparticles using the fungus Humicola sp. and its biomedical applications - Syed, Asad; Saedi, Marzouq Hussain Al; Bahkali, Ali H.; Elgorban, Abdallah M.; Kharat, Maheshkumar; Pai, Kalpana; Ghodake, Gajanan; Ahmad, Absar (Journal of Drug Delivery Science and Technology, 2021)
Synthesis of alpha-Ag2S (silver sulfide) is a highly challenging task, usually attempted using synthetic, hazardous chemical processes. This report puts efforts to exploring microbial-based eco-friendly alternatives. A facile, onepot biological method for the synthesis of alpha-Ag2S composite nanoparticles (NPs) in an aqueous medium at ambient conditions was established. As prepared alpha-Ag2S composite NPs were efficiently produced from precursors silver nitrate and sodium sulfite. The extracellular biomolecules produced by Humicola sp. reduced the precursor solution and at the same time it capped the formed Ag2S NPs. The characterization performed by different techniques revealed excellent optical, morphological, and structural properties (size, shape distribution, and crystallinity) of the alpha-Ag2S NPs. The change in color from colorless to dark brown indicated the formation of alpha-Ag2S, which was further confirmed by fluorescence and UV-Visible spectroscopy, showing a sharp peak at 410 nm. Morphological analysis of alpha-Ag2S NPs confirmed the spherical shape, and narrow size distribution. alpha-Ag2S NPs were found to be potent in antimicrobial applications owing to their high dispersibility in water and capping by extracellular biomolecules secreted by Humicola sp. The anti-cancer activity for alpha-Ag2S performed using human breast cancer cell line (ZR-75-1) and human Burkitt's lymphoma cancer (Daudi). The biocompatibility test was performed using human peripheral blood mononuclear cells (PBMCs) for alpha-Ag2S NPs. The anti-leishmania activity was also determined for alpha Ag2S NPs in-vitro using the standard anti-promastigote protocol (Leishmania donovani promastigotes). This extracellular system is an economically and environmentally benign route for the biosynthesis of alpha-Ag2S NPs having desired surface, structure and biomedical properties.
Keywords: Cytotoxicity; Fungus; Hemolysis; Humicolasp; Silver sulfide(alpha-Ag2S)